The therapeutic potential of traditional Chinese medicine in depression: focused on the modulation of neuroplasticity - Lv, Shimeng; Yang, Ni; Lu, Yitong; Zhang, Guangheng; Zhong, Xia; Cui, Yaru; Huang, Yufei; Teng, Jing; Sai, Yanyan (Frontiers in Pharmacology, 2024)
Depression, a mood disorder characterized by a persistent low mood and lack of enjoyment, is considered the leading cause of non-fatal health losses worldwide. Neuroplasticity refers to the brain's ability to adapt to external or internal stimuli, resulting in functional and structural changes. This process plays a crucial role in the development of depression. Traditional Chinese Medicine (TCM) shows significant potential as a complementary and alternative therapy for neurological diseases, including depression. However, there has been no systematic summary of the role of neuroplasticity in the pathological development of depression and TCM Interventions currently. This review systematically summarized recent literature on changes in neuroplasticity in depression and analyzed the regulatory mechanisms of active metabolites in TCM and TCM formulas on neuroplasticity in antidepressant treatment. Additionally, this review discussed the limitations of current research and the application prospects of TCM in regulating neuroplasticity in antidepressant research.